SENYAPAN DAN SELIP LIDAH TERHADAP PRODUKSI UJARAN DALAM SIDANG KE-14 JESSICA KUMALA WONGSO - Pertiwi, Poppy JJ Minang; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe trial is a process of examining and adjudicating led by judges. Implementation of the trial does not always run smoothly, often in conveying testimony in the hearing occours silence and slips of the tongue when producing an utterance. The study examines the silence and slips of the tongue in speech production found in the 14th Jessica Kumala Wongso. The method used in this research is descriptive with qualitative research form. The data source in this research is a video recording of the 14thsession Jessica Kumala wongso obtained through the youtube website. The research inventory data, which is divided into silent as much 70 times, the silence of the contents of the sound e… as much 80 times, silent content eh… as much 3 times, silent content em… as much 1 times, silent content a… as much 10 times, and silent content what as much 4 times, and progressive repetition silence 21 times, slips of the tongue as much 2 times that included in the fallacy of assembling. The researcher presents the research data of speech production that is experiencing silence and slips of the tongue equippes with session, and the actors and the intensity of speech. Keywords: Speech Production, Pause, Slips of the Tongue, The 14th Court, Cyanide Coffee Poisoning